Addressing the Challenges in Protecting Child Victims of Sexual Violence within Non-Formal Education Institutions - Dani Krisnawati; Ria Restu Wikansari (Sriwijaya Law Review)
In recent years, violence against women and children has markedly increased in the Special Region of Yogyakarta, Indonesia. Numerous cases underscore a significant potential for sexual violence against children, particularly those enrolled in non-formal education institutions. This pressing issue necessitates a thorough examination of current implementation practices, the identification of existing constraints, and the formulation of prospective criminal policies aimed at protecting children from sexual violence in these educational settings. This study utilises a socio-legal framework with a normative-empirical approach, drawing on data from Bantul Regency and Yogyakarta City. It also critically reviews pertinent regulatory frameworks and implementation practices within this context. Findings indicate that both preventive and repressive measures have been enacted to combat sexual violence against children, primarily through the empowerment of law enforcement officials and related government officers at the district, city, and provincial levels. However, the effectiveness of preventive measures is impeded by current regulations and prevailing social norms. Future initiatives to protect children from sexual violence in non-formal education institutions should prioritise non-penal approaches, including the enhancement and harmonisation of the Criminal Acts of Sexual Violence legislation at both national and regional levels. Furthermore, it reveals that local government agencies have yet to establish effective coordination mechanisms to promote better norms for preventing sexual violence in these institutions. Enhancing community empowerment and bolstering the coordination and roles of stakeholders will be pivotal in mitigating the stigma faced by child victims of sexual violence.